Les Pacifiques (1914) by Han Ryner: anti-authoritarian utopias and individualist anarchism - Queluz, Gilson Leandro (2022)
The purpose of this article is to reflect on Han Ryner's Les Pacifiques (The Pacifists), published in 1914, seeking to highlight the intersections between anti-authoritarian literary utopias and individualist anarchism. The imagined libertarian utopia was established on the island of Atlantis and is characterized by the absence of the state, the inexistence of private property, the sharing of goods, advanced technology, free love, and harmonious coexistence between human beings and nature. This utopia presents an educational political dimension in its own organization. On the other hand, it also constitutes a space for demonstrating libertarian educational experiments. The displacement brought by the cognitive estrangement triggered by this egalitarian society, based on the individualist philosophy of harmony advocated by Ryner, allows a radical and ironic critique of European civilization and capitalism, at the moment that World War I is on the horizon.